FINANCIAL LITERACY AND CULINARY SMEs - Suprihandari, Miya Dewi; Kamudu, Fitria; Haider, Ajlal (Transpublika Publisher, 2024)
Traditional food plays a significant role in the lives of people all over the world, including Indonesia. The combination of society and culinary creates a unique bond that is always fascinating to explore. Many individuals who run traditional food businesses have achieved unimaginable success, such as owning houses and vehicles. When we observe the process of these simple culinary businesses, it becomes clear that they alone cannot fulfill all of their daily needs. In this article, we will qualitatively describe the importance of accounting for the behavior of traditional Indonesian food from ancient times to the present. By examining the existing evidence, it is evident that these simple culinary businesses have thrived in the community for many decades. Accounting for the behavior of traditional Indonesian food businesses is essential for understanding their impact on the local economy and society. By studying their practices and strategies, we can gain insights into how these businesses have managed to thrive and adapt to changing market conditions.